Strengths, weaknesses, opportunities, and threats analysis of integrating the World Health Organization patient safety curriculum into undergraduate medical education in Pakistan: a qualitative case study - Misbah, Samreen (J Educ Eval Health Prof, 2017)
PURPOSE: The purpose of this study was to conduct a strengths, weaknesses, opportunities, and threats (SWOT) analysis of integrating the World Health Organization (WHO) patient safety curriculum into undergraduate medical education in Pakistan. METHODS: A qualitative interpretive case study was conducted at Riphah International University, Islamabad, from October 2016 to June 2017. The study included 9 faculty members and 1 expert on patient safety. The interviews were audiotaped, and a thematic analysis of the transcripts was performed using NVivo software. RESULTS: Four themes were derived based on the need analysis model. The sub-themes derived from the collected data were arranged under the themes of strengths, weaknesses, opportunities, and threats, in accordance with the principles of SWOT analysis. The strengths identified were the need for a formal patient safety curriculum and its early integration into the undergraduate program. The weaknesses were faculty awareness and participation in development programs. The opportunities were an ongoing effort to develop an appropriate curriculum, to improve the current culture of healthcare, and to use the WHO curricular resource guide. The threats were attitudes towards patient safety in Pakistani culture, resistance to implementation from different levels, and the role of regulatory authorities. CONCLUSION: The theme of patient safety needs to be incorporated early into the formal medical education curriculum, with the main goals of striving to do no harm and seeing mistakes as opportunities to learn. Faculty development activities need to be organized, and faculty members should to be encouraged to participate in them. The lack of a patient safety culture was identified as the primary reason for resistance to this initiative at many levels. The WHO curriculum, amended according to local institutional culture, can be implemented appropriately with support from the corresponding regulatory bodies.